Effect of aerobic exercise on tumor physiology in an animal model of human breast cancer - Jones, LW; Viglianti, BL; Tashjian, JA; Kothadia, SM; Keir, ST; Freedland, SJ; Potter, MQ; Moon, EJ; Schroeder, T; Herndon, JE; Dewhirst, MW (American Physiological Society, 2010)
Recent epidemiologic studies report that regular exercise may be associated with substantial reductions in cancer-specific and all-cause mortality following a breast cancer diagnosis. The mechanisms underlying this relationship have not been identified. We investigated the effects of long-term voluntary wheel running on growth and progression using an animal model of human breast cancer. We also examined effects on the central features of tumor physiology, including markers of tumor blood perfusion/vascularization, hypoxia, angiogenesis, and metabolism. Athymic female mice fed a high-fat diet were orthotopically (direct into the mammary fat pad) implanted with human breast cancer cells (MDA-MB-231 at 1 × 10 6 ) into the right dorsal mammary fat pad and randomly assigned (1:1) to voluntary wheel running ( n = 25) or a nonintervention (sedentary) control group ( n = 25). Tumor volume was measured every three days using digital calipers. All experimental animals were killed when tumor volume reached ≥1,500 mm 3 . Kaplan-Meier (KM) analysis indicated that tumor growth (survival) was comparable between the experimental groups (exercise 44 days vs. control 48 days; KM proportional hazard ratio = 1.41, 95% confidence interval, 0.77–2.58, P = 0.14). However, tumors from exercising animals had significantly improved blood perfusion/vascularization relative to the sedentary control group ( P < 0.05). Histological analyses indicated that intratumoral hypoxia levels (as assessed by hypoxia-inducible factor 1) were significantly higher in the exercise group relative to sedentary control ( P < 0.05). Aerobic exercise can significantly increase intratumoral vascularization, leading to “normalization” of the tissue microenvironment in human breast tumors. Such findings may have important implications for inhibiting tumor metastasis and improving the efficacy of conventional cancer therapies.